Relations Between Community Engagement Levels and Citizenship Competence Among Tertiary-Level Students at a Public Institution of Higher Education - Bastida, Ernesto L, Jr. (UI Scholars Hub, 2023)
This mixed-methods sequential explanatory study seeks to explain the relationship between community engagement and citizenship competence among tertiary-level students at Kolehiyo ng Lungsod ng Dasmariñas, a public institution of higher learning in Dasmariñas in Cavite, Philippines. Specifically, it seeks to (1) determine students’ level of engagement in various community development activities and their levels of citizenship competence; as well as (2) discuss and analyze the relationship between these two variables. Quantitative surveys were conducted on 331 students, followed by semi- structured interviews and focus group discussions with 30 purposely selected participants to gather follow-up data during the qualitative phases. The survey revealed that tertiary-level students were deeply engaged in various themes of activities, from conflict resolution, environmental sustainability initiatives, economic efficiency efforts, sports and wellness activities, disease prevention programs, food security, and nutrition awareness promotion, and gender equality initiatives. They were moderately involved in disaster risk reduction, literacy enhancement, and innovation and technology activities. Further results indicate a significant relationship between students’ community engagement and citizenship competence, and the more students are engaged in community-based activities, the more they become competent citizens. The students’ values and attitudes and displayed citizenship competence are reflected in the categories of skills, knowledge, and critical understanding. Such positive relations demonstrate how students can foster positive attitudes, learn to value humanitarianism, and help build a sustainable community through community engagement activities.